Comparative Transcriptome Analysis Identifies Key Regulatory Genes Involved in Anthocyanin Metabolism During Flower Development in Lycoris radiata - Wang, Ning; Shu, Xiaochun; Zhang, Fengjiao; Zhuang, Weibing; Wang, Tao; Wang, Zhong (Frontiers in Plant Science, 2021)
Lycoris is used as a garden flower due to the colorful and its special flowers. Floral coloration of Lycoris is a vital trait that is mainly regulated via the anthocyanin biosynthetic pathway. In this study, we performed a comparative transcriptome analysis of Lycoris radiata petals at four different development stages. A total of 38,798 differentially expressed genes (DEGs) were identified by RNA sequencing, and the correlation between the expression level of the DEGs and the anthocyanin content was explored. Meanwhile, analyses of changes in abscisic acid (ABA), brassinosteroid (BR), cytokinin, ethylene, gibberellic acid, indoleacetic acid, and methyl jasmonate levels indicated that color transitions are regulated by endogenous hormones. The DEGs involved in the ABA, auxin, BR, cytokinin, gibberellin, jasmonic acid and ethylene signaling pathways were enriched and demonstrated to be associated with petal coloring in L. radiata. The candidate genes involved in anthocyanin accumulation in L. radiata petals during flower development stages were identified, which included 56 structural genes as well as 27 key transcription factor DEGs. In addition, a key structural gene namely LrDFR1 of anthocyanin biosynthesis pathway was identified as a hub gene in anthocyanin metabolism network. During flower development stages, LrDFR1 expression level was positively correlated with the anthocyanin content. Subcellular localization revealed that LrDFR1 is majorly localized in the nucleus, cytoplasm and cell membrane. Overexpression of LrDFR1 increased the anthocyanin accumulation in tobacco leaves and Lycoris petals, suggesting that LrDFR1 acts as a positively regulator of anthocyanin biosynthesis. Our results provide new insights for elucidating the function of anthocyanins in L. radiata petal coloring during flower development.